Diseño de un sistema de control de procesos empresarial basados en indicadores de gestión y desempeño para el proceso de facturación en una empresa dedicada a la distribución y comercialización de energía eléctrica ubicada en la ciudad de Guayaquil para el año 2010 - Amores Almeida, Adriana (2011)
To design a control system based on business process management and performance indicators for the billing process for ELECTRICA S.A. were made frequent visits to the company in order to know the process and all the sub processes involved in it. Adicionally we Requested further information from the company's first half periods 2009 and 2010 which will be used in this study analysis. This work includes a theoretical framework which contains the basic concepts applicable to the development of process management system of the billing process of the company. We proceeded to develop the analytical model and design dashboard presentation of results, which were performed with analysis of the indicators. They were finally exposed the conclusions and recommendations in order to be accepted by the company to generate added value to the results of the process.